2010
DOI: 10.1111/j.1538-7836.2009.03699.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple electrode aggregometry predicts stent thrombosis better than the vasodilator‐stimulated phosphoprotein phosphorylation assay

Abstract: Summary. Background and Aim: The prognostic value of the vasodilator-stimulated phosphoprotein (VASP) phosphorylation assay and multiple electrode aggregometry (MEA) for thrombotic adverse events has been shown in independent studies. As no direct comparison between the two methods has been made so far, we investigated which laboratory approach has a better predictive value for stent thrombosis. Methods: The VASP phosphorylation assay and MEA were performed in 416 patients with coronary artery disease undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 49 publications
(77 reference statements)
4
109
0
5
Order By: Relevance
“…However, knowledge of the predictive value of the VASP-P assay in high-risk STEMI patients is missing except for one recent publication which outlined that the VASP-P assay might be helpful in predicting cardiovascular death above a cut-off of PRI=61% in unselected patients (43). The high sensitivity (93.8%) as well as the low specificity (39.8%) of the VASP-P assay in our study is comparable with earlier findings (8,11). It has recently been shown that levels of P2Y 12 -blockade above 60% are required to block the effects of ADP on PGE 1 -induced phosphorylation of VASP (44).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, knowledge of the predictive value of the VASP-P assay in high-risk STEMI patients is missing except for one recent publication which outlined that the VASP-P assay might be helpful in predicting cardiovascular death above a cut-off of PRI=61% in unselected patients (43). The high sensitivity (93.8%) as well as the low specificity (39.8%) of the VASP-P assay in our study is comparable with earlier findings (8,11). It has recently been shown that levels of P2Y 12 -blockade above 60% are required to block the effects of ADP on PGE 1 -induced phosphorylation of VASP (44).…”
Section: Discussionsupporting
confidence: 81%
“…However, previous studies have shown that MEA is predictive for stent thrombosis and death in patients with planned DES implantation (9,39). Others showed that MEA predicts stent thrombosis better than the VASP-P assay (8). Interestingly, the conclusion of the latter study was mainly based on ROC curves from three definite stent thromboses.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Antiplatelet drugs differ in their pharmacokinetic and pharmacodynamic characteristics. Current guidelines recommend stopping antiplatelet drugs 3 to 7 days before surgery [8][9][10], however a proportion of individuals are 'resistant' to aspirin or the P2Y 12 antagonist or both [11][12][13]. The Society of Thoracic Surgeons Clinical Practice Guidelines (updated in 2012) states: "for patients on dual antiplatelet therapy, it is reasonable to make decisions about surgical delay based on tests of platelet inhibition rather than arbitrary use of a specified period of surgical delay" [14].…”
Section: Drivers F or Preoperative Plat Elet Function Testingmentioning
confidence: 99%
“…To strengthen our findings we also applied in the calculations other clinically validated HTPR definitions (PRI > 60% [16,17] and AUC > 54 U [18] for VASP and MEA, respectively).…”
Section: Study Definitions and Endpointsmentioning
confidence: 99%